Performance of the State Civil Apparatus in the General Administration and Personnel Section at the Sawahlunto City Population Control and Family Planning Health Service - Nazirwan Nazirwan; Fadhlan Fadhlan (STIA Adabiah, 2024)
Performance in the context of work refers to the outcome attained by an individual when carrying out assigned activities. It is influenced by factors such as skill, experience, dedication, and adherence to deadlines, all to achieve organizational objectives. Performance can be assessed by evaluating the level of quality, the amount of output produced, and the adherence to deadlines: collaboration and mutual assistance. The employee's performance aligns with the assigned tasks. Quantity refers to the specific amount that needs to be attained or generated, such as the quantity of rupiah, units, or completed activity cycles. Timeliness refers to the extent to which an action is finished according to the intended timeframe, considering the synchronization with other outcomes and the time availability for different tasks. Researchers employ qualitative research methodologies. This study uses a descriptive research approach, which involves conducting research to provide an unbiased and factual depiction of a given scenario. This strategy is employed to resolve or address the challenges encountered in the present scenario, specifically the factors under investigation. The research findings indicate that employee performance is characterized by high quality and quantity of work, adherence to well-defined targets, and adherence to work standards or primary responsibilities of each employee. Additionally, the task is evenly allocated among all staff members. The execution was timely and efficient, and the teams collaborated substantially. Communication is excellent, and there is a mutual contribution from all parties involved. The identified obstacles encompass insufficient infrastructure and personnel. Efforts to surmount these barriers involve strategizing the acquisition of laptops and computers with upgraded specs, offering training, and fostering expertise, particularly in technology utilization. This approach aims to enhance the performance of ASN.